Inquiring Electricity in Primary School: A Non-Formal Teaching Education Case Study. Issue 1 (1st June 2022) - Adesso, M G; Capone, R; Fiore, O
Abstract: In this paper we describe a primary school teachers' training project which includes laboratory activities as part of non-formal education curricula. Fifty teachers and three researchers in the South of Italy were involved in the project. Some inquiry activities were proposed, while teachers and researchers co-planned some further laboratory activities and experiments, all of which were carried out with 9-10 aged pupils. In the case study described, children used artifacts made from simple and low-cost materials, and transformed them into instruments to experiment with electrical phenomena. By observing the researcher who directly acted in the classroom and actively attended the students during the laboratory phases, the teachers improved their professional knowledge in teaching Physics through laboratory activities within a non-formal environment.